Design of Pond Water Temperature Monitoring Built Using NodeMCU ESP8266 - Muhammad, Saiful Azhari; Haryono, Haryono (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Freshwater fish farming is currently booming in Indonesia, and many use small ponds for efficiency or due to limited location, this can be a problem due to Indonesia's hot climate. Small ponds with not much water volume will cause the water temperature to rise more easily on hot days, of course this is not good for the fish colonies in it. To prevent temperature rise, farmers generally irrigate ponds with fresh water to stabilize the water temperature. Due to the unpredictable weather in Indonesia lately, it will be difficult for farmers to monitor their ponds manually, so a tool is needed that can detect the heat of pond water and turn on the water pump to irrigate ponds. This research is expected to make it easier for farmers to regulate pond temperatures more easily. The use of a microcontroller in Internet of Thing devices is very much needed, considering that the microcontroller is able to carry out the task of controlling the existing sensors. The sensor used in this study uses a temperature sensor that is used to control the pool water. The prototype for detecting pool water temperature and increasing water flow is used to reduce heat in pool water and increase water flow that is reduced due to evaporation of water during the day. The purpose of this research is to make a prototype to detect pond water temperature and increase pond water discharge which is useful for reducing pond water temperature to be cooler and reducing the risk of fish death. The prototype developed is a NodeMCU ESP 8266 micro-controller, a temperature detection sensor in water, a relay as a switch and a mini pump